Pengaruh Kompetensi Guru dan Kecerdasan Emosional Terhadap Kinerja Guru Sekolah Dasar - Aswanrahman Aswanrahman; Muh Yunus; Elpisah Elpisah (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This study aims to determine the effect of teacher competence and emotional intelligence on the performance of elementary school teachers. The type of research that the researcher uses is quantitative research with an expost facto approach. The population, namely all teachers at SDN 587 Mataluntun, amounted to 10 people. The sample uses (total sampling) so the sample is 10 people. Data collection by lift, documentation. Data analysis used descriptive statistical analysis. The results of the study indicate that there is a positive and significant influence both partially and simultaneously between the variables of teacher competence and emotional intelligence on the performance of teachers at SDN 587 Mataluntun.